The Role of Television News Headlines in Attracting Viewers to News Bulletins: A Field Study from 01/01/2023 to 31/03/2023 - Hussain, Yousif Muhammed (ALBAHITH ALALAMI, 2023)
The objective of this study is to ascertain the pivotal role of headlines in captivating viewers' attention toward news bulletins. Additionally, it aims to explore the factors that contribute to the correlation between headlines and the public's acceptance or rejection of the meticulously crafted news articles presented through these bulletins. The study delves into the mechanisms employed in writing and editing headlines, focusing on their style, expert composition, and intriguing nature. These factors inevitably influence the level of acceptance and engagement of the viewership with the news articles disseminated via the news bulletins. Employing a descriptive methodology, the researcher distributed 200 questionnaires to examine and delve into the thoughts and inclinations of the public regarding the subject matter. The study yielded a collection of noteworthy findings, including the significant interest displayed by the audience in following the primary headlines of news bulletins. The headline emerges as a pivotal element that entices the audience, compelling them to remain tuned in to the news bulletins. Notably, the audience's interest in news headlines is profoundly impacted by their formulation and composition, employing an enticing and captivating style mastered by the journalists.